The Penerapan Teknik Animasi Flat Morphin Dalam Video Edukasi ‘Green Log : Where The Package Meets Planet’ Untuk Visualisasi Dampak Logistik Terhadap Lingkungan - Ahmadsyah Farras Fauzan; Toto Sugito; Heru Ryanto Budiana (Pusat Riset dan Inovasi Nasional, 2025)
The animated work Green Log: Where The Package Meets Planet, explores the environmental impact of urban logistics activities through a minimalist yet informative flat design visual approach, utilizing actual air quality data (Jakarta AQI), delivery vehicle emission patterns, as well as case studies of sustainable solutions such as the implementation of electric vehicles in the IKN and global practices of companies such as Amazon. The creation process begins with quantitative research on logistics-related pollution patterns, the development of visual narratives based on motion graphics principles with graphic match-cut techniques for symbolic transitions between problems and solutions, to the production of 2D animations that optimize the green-blue color palette and simple geometric elements to convey the complexity of environmental issues more easily digested. The final result, a 3-minute animated video, not only visualizes the relationship between 166 million monthly deliveries and the degradation of Jakarta's air quality, but also offers a solution perspective through the visualization of the transformation of conventional logistics systems towards sustainable models, with the hope of increasing public awareness and encouraging discussions about green transportation policies in Indonesia